2019
DOI: 10.1186/s12885-019-6327-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtyping improves prognostication of Stage 2 colorectal cancer

Abstract: BackgroundPost-surgical staging is the mainstay of prognostic stratification for colorectal cancer (CRC). Here, we compare TNM staging to consensus molecular subtyping (CMS) and assess the value of subtyping in addition to stratification by TNM.MethodsThree hundred and eight treatment-naïve colorectal tumours were accessed from our institutional tissue bank. CMS typing was carried out using tumour gene-expression data. Post-surgical TNM-staging and CMS were analysed with respect to clinicopathologic variables … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
14
1
Order By: Relevance
“…Moreover, patients with MSI and CMS1 have a better OS and RFS compared to CMS2-4. Contrary to previous results, Purcell et al [ 39 ] reported that stage II patients with CMS3 had a worse prognosis in OS than patients in CMS1-2, although an imbalance between CMS groups, with few CMS4 patients, could explain this result. Besides the possibility for CMS to determine CRC subtypes with worse prognosis for proposing personalized treatments, CMS still needs more studies to define the differences in the prognosis of patients through the different TNM stages of CRC.…”
Section: Cms and Prognosiscontrasting
confidence: 63%
“…Moreover, patients with MSI and CMS1 have a better OS and RFS compared to CMS2-4. Contrary to previous results, Purcell et al [ 39 ] reported that stage II patients with CMS3 had a worse prognosis in OS than patients in CMS1-2, although an imbalance between CMS groups, with few CMS4 patients, could explain this result. Besides the possibility for CMS to determine CRC subtypes with worse prognosis for proposing personalized treatments, CMS still needs more studies to define the differences in the prognosis of patients through the different TNM stages of CRC.…”
Section: Cms and Prognosiscontrasting
confidence: 63%
“…As mentioned above, earlier efforts to implement a CMS classification in a clinical setting have failed, probably due to the robust methodology needed and the lack of prognostic or predictive capabilities, especially with CMS2 and CMS3, which at times comprise more than 50% of the population [ 87 ]. Additionally, in early-stage CC, the number of mesenchymal subtypes (CMS4) is very low, and they sometimes comprise groups with too few events to enable a meaningful statistical analysis [ 18 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…CMS is a stratification system based on the biological characteristics of CRC patients that has recently emerged [ 47 ]. Recently, Purcell et al suggested that consensus molecular subtyping is used, as it improves the prognosis of TNM II stage CRC patients [ 48 ]. Our results show that TNM II stage patients can be sub-grouped into two distinct strata, with different survival probability: patients with lower circ-BCL2L12-1 levels show longer OS intervals, close enough to those of TNM I stage patients, while patients with higher circ-BCL2L12-1 levels show shorter OS intervals, even shorter than those of TNM III stage patients ( Figure 4 b).…”
Section: Discussionmentioning
confidence: 99%